A real-time Energy Management System for the integration of economical aspects and system operator requirements: Definition and validation. (March 2017) - Bendato, Ilaria; Bonfiglio, Andrea; Brignone, Massimo; Delfino, Federico; Pampararo, Fabio; Procopio, Renato
Abstract: The present paper proposes a real-time EMS able to manage uncertainties in the forecasting data as well as economical aspects and system operator requirements. As far as the first aspect is concerned, the procedure is cyclically repeated at each time-step after that loads and renewable productions have been adjusted by means of real-time measurements. The economic aspects are performed by solving an optimization problem that minimizes the overall production cost and, therefore, it fixes the active power set point for all the programmable units. The Distribution System Operator (DSO) requirements in terms of active/reactive power management and voltage control, as requested by the majority of grid codes/standards, are satisfied (if possible) by tuning the reactive power of the programmable units. The proposed EMS has been applied and validated on University of Genoa Smart Polygeneration Microgrid (SPM) and it shows its efficacy in satisfying both the economic and power quality objectives. Highlights: A real-time EMS able to manage uncertainties in the forecasting data. Integration of the economical aspects and system operator requirements. A two-frame algorithm. Application and validation on University of Genoa Smart Polygeneration Microgrid (SPM).